2017
DOI: 10.1007/s00403-017-1720-9
|View full text |Cite
|
Sign up to set email alerts
|

Laser and light-based therapy for cutaneous and soft-tissue metastases of malignant melanoma: a systematic review

Abstract: Invasive cutaneous melanoma is a growing health concern. Although surgical excision can effectively treat in situ tumors, use for metastatic melanoma is limited. Laser and light-based therapies may be a valuable palliative treatment option for patients with stage III and stage IV cutaneous metastatic melanoma. Our goal is to review the published literature and provide evidence-based recommendations on laser and light-based palliative therapies for metastatic melanoma. A search of the databases Pubmed, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 45 publications
0
21
0
1
Order By: Relevance
“…We observed that microscopic satellitosis does not necessarily translate into the lymphovascular infiltration of the tumour [ 13 ]. In one study, the 5-year overall and disease-free survivals in patients with microscopic satellitosis were 34% and 18%, respectively, demonstrating an unfortunate prognosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that microscopic satellitosis does not necessarily translate into the lymphovascular infiltration of the tumour [ 13 ]. In one study, the 5-year overall and disease-free survivals in patients with microscopic satellitosis were 34% and 18%, respectively, demonstrating an unfortunate prognosis [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a light-based therapy. It represents a promising adjuvant treatment and can be used as a palliative method of choice for patients with stage III/IV cutaneous metastatic melanomas [24]. PDT is considered a minimally invasive procedure that requires a photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…PDT is considered a minimally invasive procedure that requires a photosensitizer. Absorption is superior in metabolically active tissues [24]. The method applies non-toxic compounds, which create reactive oxygen species (ROS) when combined with oxygen [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several lasers have been used to treat melanocytic proliferations, such as CO 2 , Q-switched ruby, Nd:YAG, argon, and alexandrite [12][13][14] . These lasers have been used for palliative treatment of melanoma metastases, but they are not ordinarily used for therapy of primary melanoma [ 15 ] .…”
Section: Introductionmentioning
confidence: 99%